The Bourne supremacy - Ludlum, Robert, 1927-2001. (New York : Random House, 1986)
Deciding that Jason Bourne must find his own murderous imposter, Jason follows the kidnapper's trail to treacherous Hong Kong.
Keywords: Carlos, -- the Jackal -- Fiction; United States. -- Central Intelligence Agency -- Fiction; Bourne, Jason (Fictitious character) -- Fiction; Terrorists -- Fiction; Adventure fiction; Spy stories